Acoustic and volumetric properties of aqueous solution of levofloxacin nickel complexes at 308K - Das, Monalisa; Das, Smrutiprava; Patnaik, Ajaya (International Journal of Advanced Chemistry, 2014)
The density and ultrasonic velocity were measured for aqueous solutions of nickel complex and its ternary complex with 1,10-phenanthroline at 308 K. Using the experimental data, adiabatic compressibility , acoustic impedance , intermolecular free length and hydration number , apparent molar volume , limiting apparent molar volume , apparent molar compressibility , limiting apparent molar compressibility and their associated constants were calculated. These parameters were used to study the ion-solvent interaction in each solution.   Keywords: Ultrasonic Velocity, Hydration Number, Adiabatic Compressibility, Apparent Molar Volume, Apparent Molar Compressibility.